The moon looked down [large type] - Garlock, Dorothy (Thorndike Press large print basic, 2009)
Sophie Heller's family emigrated from Germany to Victory, a small town in Illinois, before World War II began. Now that the war has affected the town, the townspeople discriminate against Sophie and her family. When a train derails by accident, the Heller family is blamed. A teacher from the local high school comes to Sophie's rescue, and despite their cultural differences, a romance starts to bloom.